AtMYB72 aggravates photosynthetic inhibition and oxidative damage in Arabidopsis thaliana leaves caused by salt stress - Hongrui Zhang; Yinuo Wu; Hongbo Zhang; Nan Sun; Hongjiao Zhang; Bei Tian; Tanhang Zhang; Kexin Wang; Xu Nan; Huiui Zhang (Plant Signaling & Behavior)
MYB transcription factor is one of the largest families in plants. There are more and more studies on plants responding to abiotic stress through MYB transcription factors, but the mechanism of some family members responding to salt stress is unclear. In this study, physiological and transcriptome techniques were used to analyze the effects of the R2R3-MYB transcription factor AtMYB72 on the growth and development, physiological function, and key gene response of Arabidopsis thaliana. Phenotypic observation showed that the damage of overexpression strain was more serious than that of Col-0 after salt treatment, while the mutant strain showed less salt injury symptoms. Under salt stress, the decrease of chlorophyll content, the degree of photoinhibition of photosystem II (PSII) and photosystem I (PSI) and the degree of oxidative damage of overexpressed lines were significantly higher than those of Col-0. Transcriptome data showed that the number of differentially expressed genes (DEGs) induced by salt stress in overexpressed lines was significantly higher than that in Col-0. GO enrichment analysis showed that the response of AtMYB72 to salt stress was mainly by affecting gene expression in cell wall ectoplast, photosystem I and photosystem II, and other biological processes related to photosynthesis. Compared with Col-0, the overexpression of AtMYB72 under salt stress further inhibited the synthesis of chlorophyll a (Chla) and down-regulated most of the genes related to photosynthesis, which made the photosynthetic system more sensitive to salt stress. AtMYB72 also caused the outbreak of reactive oxygen species and the accumulation of malondialdehyde under salt stress, which decreased the activity and gene expression of key enzymes in SOD, POD, and AsA-GSH cycle, thus destroying the ability of antioxidant system to maintain redox balance. AtMYB72 negatively regulates the accumulation of osmotic regulatory substances such as soluble sugar (SS) and soluble protein (SP) in A. thaliana leaves under salt stress, which enhances the sensitivity of Arabidopsis leaves to salt. To sum up, MYB72 negatively regulates the salt tolerance of A. thaliana by destroying the light energy capture, electron transport, and antioxidant capacity of Arabidopsis.